Physicochemical properties and pozzolanic performance of ultrafine treated rice husk ash (uftrha) as additive in concrete - Saad, Siti Asmahani; Shafiq, Nasir; Ali, Maisarah (Malaysian Institute of Planners, 2018)
Rice husk ash (RHA) contains high amount of amorphous silica that is ubiquitous in the pozzolanic reaction of SCM in concrete. However, usage of conventional RHA is currently unfavourable in concrete industry due to its properties inconsistency. In this regard, improvement on the RHA properties by introduction of thermochemical pre-treatment prior to burning procedure is seen as an excellent way to reach the goal. In this paper, raw rice husk was pre-treated using 0.1N hydrochloric acid (HCl) and heated at 80oC. It was then mechanically activated by high energy planetary ball mill for 15 minutes at speed of 300rpm and ball-to-powder ratio (BPR) of 15:1. The chemical composition, mineralogical properties, particle size analysis, specific surface area as well as microstructure properties of ultrafine treated rice husk ash (UFTRHA) were determined accordingly. As for amorphous silica content of the optimum sample was recorded as 98.60% incinerated at 600oC with four hours of pre-treatment soaking duration. In terms of particle size and specific surface, it was also observed that, burning temperature of 600oC, pre-treated at four hours were recorded to produce finest size of UFTRHA where d(0.1), d(0.5) and d(0.9) were obtained as 1.416 μm, 4.364 μm and 14.043 μm respectively. Largest specific surface area value was obtained at 219.58 m2/g with the similar pre-treatment conditions. Meanwhile, the strength activity of UFTRHA from the optimum pre-treatment process was measured by testing the compressive strength of mortars. The highest compression value obtained was 50.17MPa with 3% UFTRHA replacement at 28 days.